SPIRITUAL HARMONY: THE ROLE OF LOCAL TRADITION IN BUILDING INTERFAITH TOLERANCE IN SENGIR - Hadziq, Abdulloh; Muqronul Faiz, Mohammad; Fadhliyah, Lia (Harmoni, 2024)
AbstractThis research aimed to explore the inter-religious harmony built through tradition, culture, and local wisdom in Sengir Hamlet, Kulon Progo, Yogyakarta. Sengir is a multireligious community with Muslim and Christian residents who can maintain tolerance and harmony in daily life. Using qualitative and phenomenological approaches, this research revealed that local traditions such as Suran, Saparan, Rejeban, and death prayers are important in building spiritual harmony. These traditions not only are a space for social interaction but also reflect the values of pluralism and religious moderation. The results showed that the Sengir community's understanding of religion and culture is inclusive, which allows them to coexist peacefully despite having different beliefs. The leadership of religious, customary, and community leaders contributes to maintaining this harmony. This research contributes to the literature on diversity management and the importance of interfaith dialog based on local wisdom as a strategic solution in creating a harmonious and inclusive society.